Pengaruh Efikasi Diri Terhadap Kecemasan Presentasi Siswa Kelas XI di SMA Negeri 1 Wuryantoro - Jendra, Arya Firmanu; Sugiyo, Sugiyo (IAIN Kudus, 2020)
Effect of Self-Efficacy on Anxiety Presentation of Class XI Students in SMA Negeri 1 Wuryantoro. This research was conducted based on social phenomena, namely the high level of anxiety when presentations in the learning process in class caused by low confidence in the abilities possessed by students. The purpose of this study was to determine the effect of self-efficacy on presentation anxiety in class XI students at Senior High School 1 Wuryantoro. This study uses a correlational quantitative research design. The population in this study were students of class XI in Senior High School 1 Wuryantoro totaling 230 students with a sample of 160 students. The sample selection is done by simple random sampling technique. Data collection tools used in this study were self-efficacy scale and presentation anxiety scale. Based on the results of a simple regression analysis that self-efficacy variables affect the presentation anxiety variable by 8.6%, while the remaining 91.4% is influenced by other factors not explained in this study. The coefficient score of the effect of self-efficacy on packaging presentations shows a score that has a negative direction. This can be interpreted that the higher the self-efficacy, the lower the presentation anxiety and vice versa. Keywords: Anxiety; Self Efficacy; Students